The Role of Leadership, Motivation, Work Discipline, and Compensation in Improving Employee Performance at PT Kereta Api Indonesia (Persero) Daop IV Semarang - Aditya Catur Siwi; Dhanan Abimanto; Adenanthera Lesmana Dewa (Indonesian Maritime Researchers and Lecturers, 2025)
This study aims to analyze the significant role of leadership, motivation, work discipline, and compensation in improving employee performance at PT Kereta Api Indonesia (Persero) Daop IV Semarang. This research adopts a quantitative associative approach, providing a clear understanding of the key factors that influence employee performance. Data were collected through a Likert-scale questionnaire, which was distributed to 80 respondents who are permanent employees of Daop IV Semarang. The data analysis was carried out using SPSS version 26, which included validity and reliability tests, as well as multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results reveal that leadership, motivation, work discipline, and compensation all have a positive and significant impact on employee performance. Among these variables, motivation was found to be the most dominant factor influencing performance. This finding suggests that fostering higher motivation and effective leadership can significantly enhance employee performance. This research provides practical implications for PT KAI management to enhance productivity through strengthening discipline culture, implementing fair compensation systems, and promoting participative leadership styles.